2014
DOI: 10.1155/2014/759039
|View full text |Cite
|
Sign up to set email alerts
|

Potent Antioxidative and UVB Protective Effect of Water Extract ofEclipta prostrataL.

Abstract: Oxidative stress, including Ultraviolet (UV) irradiation-induced skin damage, is involved in numerous diseases. This study demonstrates that water extract of Eclipta prostrata L. (WEP) has a potent effect in scavenging 1,1-diphenyl-2-picrylhydrazyl (DPPH), superoxide radicals, and chelating ferrous ion, exhibiting IC50 values of 0.23 mg/mL, 0.48 mg/mL, and 1.25 mg/mL, respectively. The WEP total phenol content was 176.45 mg gallic acid equivalents (GAE)/g sample. Chlorogenic acid, a component of the plant's ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…In synopsis, our outcomes show that Eclipta alba has colossal potential in reciprocal and elective drug for the treatment of malignant growth. [7] Kim HY et al have been reported another terthiophene, 3'-hydroxy-2,2':5',2″-terthiophene-3'-O-β-Dglucopyranoside (1) and another oleanane-type saponin, echinocystic corrosive 3-O-(6-O-acetyl)-β-Dglucopyranoside (7) were disconnected from the flying parts of Eclipta prostrata L. Additionally, five thiophenes (2-6), seven triterpenoids (8)(9)(10)(11)(12)(13)(14), two coumestans (15 and 16), and four flavonoids (17)(18)(19)(20) having recently realized synthetic structures were secluded amid a similar course of this examination. All the disconnects 1-20 were assessed for their cytotoxicity against human ovarian disease cells (SKOV3) utilizing MTT measures.…”
Section: Anti Inflammatory Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In synopsis, our outcomes show that Eclipta alba has colossal potential in reciprocal and elective drug for the treatment of malignant growth. [7] Kim HY et al have been reported another terthiophene, 3'-hydroxy-2,2':5',2″-terthiophene-3'-O-β-Dglucopyranoside (1) and another oleanane-type saponin, echinocystic corrosive 3-O-(6-O-acetyl)-β-Dglucopyranoside (7) were disconnected from the flying parts of Eclipta prostrata L. Additionally, five thiophenes (2-6), seven triterpenoids (8)(9)(10)(11)(12)(13)(14), two coumestans (15 and 16), and four flavonoids (17)(18)(19)(20) having recently realized synthetic structures were secluded amid a similar course of this examination. All the disconnects 1-20 were assessed for their cytotoxicity against human ovarian disease cells (SKOV3) utilizing MTT measures.…”
Section: Anti Inflammatory Activitymentioning
confidence: 99%
“…These outcomes proposed that some particular mixes or concentrates from E. prostrata are potential wellsprings of normal enemy of tumor materials and deserving of further examination. [19] Chan CF et al have been reported the oxidative pressure, including Ultraviolet (UV) illumination actuated skin harm, is associated with various illnesses. This examination exhibits that water concentrate of Eclipta prostrata L. (WEP) has a strong impact in searching 1,1-diphenyl-2-picrylhydrazyl (DPPH), superoxide radicals, and chelating ferrous particle, showing IC50 estimations of 0.23 mg/mL, 0.48 mg/mL, and 1.25 mg/mL, individually.…”
Section: Anti Inflammatory Activitymentioning
confidence: 99%
“…Eclipta prostrata is an annual herb of the Asteraceae family that is native to China, Japan, and India; it is commonly used as a Chinese herbal medicine to treat many diseases . For example, Chan et al found that the water extract of E. prostrata had antioxidant effects, and Ryu et al used the cells of RAW 264.7 macrophages to clarify that the anti‐inflammatory and antioxidant properties of E. prostrata extract were related to the expressions of iNOS, TNF‐α, and IL‐6 . Additionally, animal experiments revealed that E. prostrata extract has hypolipidemic effects .…”
Section: Introductionmentioning
confidence: 99%
“…Eclipta prostrata L. (Mohanlian in Chinese) is an annual herbaceous plant. It belongs to the Compositae family and is widely distributed in tropical and subtropical areas (Chan, Huang, Guo, & Wang, ; Kim et al, ; Park et al, ). E. prostrata has been used as a traditional Chinese medicine to treat various symptoms for thousands of years in China, for example, spitting blood, hematuria, loose teeth, dizziness, tinnitus and hepatic disorders (Karthikumar, Vigneswari, & Jegatheesan, ; Kumari, Govindasamy, & Sukumar, ; Liu et al, ; Liu, Zhao, Zhong, & Jiang, ; Pukumpuang, Chansakaow, & Tragoolpua, ; Thakur & Mengi, ; Zhao et al, ).…”
Section: Introductionmentioning
confidence: 99%